Moving Imagination : Explorations of Gesture and Inner Movement - Preester, Helena De (Advances in consciousness research, 2013)
To know anything in space (for instance, a line), I must draw it, and thus synthetically bring into being a determinate combination of the given manifold, so that the unity of this act is at the same time the unity of consciousness (as in the concept of a line); and it is through this unity of consciousness that an object (a determinate space) is first known. Immanuel Kant, Critique of Pure Reason, B 138 (2007).